Implantação da gestão da assistência farmacêutica no município de Arujá - Ceschini, Simeri Bernardo Castanheira (2010)
The Pharmaceutical Assistance Service at SUS is going through a decentralization process. The Pharmaceutical Assistance Management Service has been implemented in Arujá city with the intention of contributing with practical services as well as rationalizing the work process, which has brought about a management reformulation. In order to provide wholesome actions toward health assistance it was necessary to add values to such actions through Pharmaceutical Assistance development; to have highly qualified professionals; to select a thorough medicament list which could meet the primary needs of the region epidemiological profile; to ensure quality, and to provide the most of medical prescriptions; all that allied with the adequate and rational use and promotion of such medical prescriptions. Pharmaceutical Assistance service guidelines available today are those assisted by Federal, State and Municipal government institutions depending strictly on the actions of each manager in such a way that that it promotes the Public Policies,which exists to meet the needs of each region and local needs always following established SUS standard guidelines. It seems crucial to highlight the political, economical and administrative limitations in the process of structural adjustment, which influences directly on the quality, access and humanization process. The present work has had as its main goal to compare and report the SUS Pharmaceutical Assistance Service implementation in Arujá city by means of interviews with users and employees both before and after the Pharmaceutical Assistance Management Service program implementation. For such program implementation it was necessary to elaborate The Pharmaceutical Assistance Guideline and The 5S Program which aimed at organizing the services and medicament actions related to all its broad dimensions as well as prioritizing the users and the community in relation to health promotion. The program implementation also focused on the various activities and actions that pharmaceutical care could provide for the population involved and the rational use of medications. There was an intensive health training program for the professionals and the elaboration of manuals and guidelines with standardized medications and the implementation of The 5S Program, which aimed at reorganizing the services and adopting strategies to improve the access and the quality for users, trying to find original user-friendly solutions and achieving significant improvement on services. It would be possible if it could raise the level of trust, responsibility and quality at the workplace. The change in relation to the organization and action management directly influenced the service quality and the satisfaction level by the users. All the favorable aspects reported on this present work have demonstrated a significant level on the amount of dispensed prescriptions for the users totalizing 105, 27% of the medicament assistance; 145,27% on financial investments used to purchase medicaments and the restructuring on the services provided on the Pharmaceutical Assistance program, humanizing, organizing and ensuring qualified medicament treatments for the users.